Fe2O3 Review: Nanostructure, Synthesis Methods, and Applications - Novita, Novita; Ramlan, Ramlan; Naibaho, Marzuki; Ginting, Masno; Humaidi, Syahrul; Duma, Tulus Na (Ridwan Institute, 2024)
Iron sand, which contains magnetite iron ore, exhibits unique magnetic properties when exposed to magnetic fields. Iron ore content, including ?-Fe2O3, FeTiO3, Magnetite (Fe3O4), and others, provides potential uses in various industries such as electronics, energy, chemical, ferrofluids, catalysts, and biomedicine. The location of the discovery of iron sand can affect its mineral characteristics and geological conditions. This research aims to develop innovative synthesis methods to produce hematite nanomaterials from iron sand. Nano-size hematite nanoparticles exhibit unique characteristics, including an increase in specific surface area that is beneficial in applications such as gas sensors, catalysts, lithium-ion batteries, and the manufacture of permanent magnets. Through a literature review, this article presents comprehensive insights into the characteristics of iron sand, variations in synthesis methods, and the structure of hematite nanoparticles. Applications of hematite nanoparticles in water treatment, catalysis, and energy storage are also detailed. This article is expected to contribute to the development of innovative nanomaterial technologies as well as explore the potential of iron sand resources for wider industrial applications.